Entrepreneurship Courses’ Impact on Students’ Interest in Entrepreneurship - Primadona (International Journal of Science and Society, 2019)
The economic difficulties in 1998 with the monetary crisis that occurred in the transformation era caused a lot of unemployment in various places in Indonesia. The cause of this high unemployment is the imbalance of fairly high population growth with the few available jobs. This research then aims to see how entrepreneurship lectures for students can influence entrepreneurial interest. This research will be carried out using quantitative methods. Existing data will be analyzed using descriptive analysis and multiple linear regression. This study found that entrepreneurship lectures influenced students’ interest in doing entrepreneurship. The effects of this lecture are divided into two, namely the lecture material and how to deliver the material. The lecture material directly influences student interest, while the way this material is delivered does not directly affect student interest in entrepreneurship.